2007
DOI: 10.1111/j.1532-5415.2007.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Kenosha County Falls Prevention Study: A Randomized, Controlled Trial of an Intermediate‐Intensity, Community‐Based Multifactorial Falls Intervention

Abstract: This multifactorial intervention did not decrease falls in at-risk community-living adults but did decrease nursing home utilization. There was evidence of efficacy in the subgroup who had an MMSE score of 27 or less and lived with a caregiver, but validation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
12

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 25 publications
(44 reference statements)
1
60
0
12
Order By: Relevance
“…" (Clemson et al, 2004;Mahoney et al, 2007;Salminen, Vahlberg, Salonoja, Aarnio, & Kivela, 2009;ShumwayCook et al, 2007)의 구체적인 내용은 다음과 같다. …”
Section: ) 제3가설unclassified
See 1 more Smart Citation
“…" (Clemson et al, 2004;Mahoney et al, 2007;Salminen, Vahlberg, Salonoja, Aarnio, & Kivela, 2009;ShumwayCook et al, 2007)의 구체적인 내용은 다음과 같다. …”
Section: ) 제3가설unclassified
“…낙상을 예방하기 위한 중재는 근력강화운동, 음악과 함께 하는 좌식운동, 유연성 및 균형운동, 스트레칭 및 점진적 율동운동, 태극 운동, 탄성밴드를 이용한 운동 (Liu & So, 2008;Nelson et al, 2004;Rejeski et al, 2008;Shumway-Cook et al, 2007)과 교육, 환경수정요법 과 영양보충요법 등 (Clemson et al, 2004;Mahoney et al, 2007;Tinetti, Richman, & Powell, 1990 …”
unclassified
“…Falls among adults aged 65 years and older are a leading cause of disability, morbidity, and death, with sufferers occasionally requiring special medical or nursing care for injuries, resulting in a subsequent decrease in quality of life (Centers for Disease Control and Prevention, 2011;Costello & Edelstein, 2008;Lord, Ward, Williams, & Anstey, 1994;Mahoney et al, 2007;Rubenstein & Josephson, 2002). In a single year, 20-30% of Japanese older adults and approximately one third of adults from other countries aged 65 years and over, and 50% of those aged 80 years and over, experienced falls (Berg, Alessio, Mills, & Tong, 1997;Campbell et al, 1990; Centers for Disease Control and Prevention, 2011;Kamei, Kajii, Itoi, Yamada, & Niino, 2009;Niino, Tsuzuku, Ando, & Shimokata, 2000;Rubenstein & Josephson, 2002;Yasumura et al, 1994;Yasumura & Hasegawa, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Multifactorial intervention programs for older adults have proved effective for preventing falls (American Geriatrics Society, British Geriatrics Society & American Academy of Orthopaedic Surgeons Panel on Falls Prevention, 2001; Costello & Edelstein, 2008;Day et al, 2002;Gillespie et al, 2012;Mahoney et al, 2007;Tinetti et al, 1994). Recent studies have shown that multifactorial interventions including home hazard, safety assessments, and home modifications are beneficial for decreasing the rate of falls in the community elderly strongly supporting the importance of home hazard reduction (Costello & Edelstein, 2008;Gillespie et al, 2012;Kamei, Kajii, Itoi, Kozakai, & Niino, 2010;Newton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The most common interventions featured in successful multifactorial intervention studies are exercise, medication review, an assessment of vision, hearing, cardiovascular function and psychological state with proper referrals, and an assessment of the home environment and assistive devices (Close et al, 1999, Davison et al, 2005, Jensen et al, 2002, Spice et al, 2009, Tinetti et al, 1994, AGS/BGS, 2010, AGS/BGS/AAOS, 2001. Efficacy of such interventions varies, and in some multifactorial intervention studies no reduction in falls could be shown (de Vries et al, 2011, Mahoney et al, 2007. Thus there is room for improvement and further research concerning this complex problem.…”
Section: Falls Prevention Initiativesmentioning
confidence: 99%